Practical synthesis of phthalimides and benzamides by a multicomponent reaction involving arynes, isocyanides, and CO2/H2O - Kaicharla, Trinadh; Thangaraj, Manikandan; Biju, Akkattu T. (Organic Letters, 2014)
Transition-metal-free multicomponent reactions involving arynes and isocyanides with either CO2 or H2O have been reported. With CO2 as the third component, the reactions resulted in the formation of N-substituted phthalimides. The utility of water as the third component furnished benzamide derivatives in moderate to good yields. These reactions took place under mild conditions with broad scope.